Unlocking Potential: Digital Transformation and Decision Support in Automotive Repair - A Case Study - Natalia Natalia; Pri Hermawan (Research Synergy Foundation, 2024)
In today's rapidly evolving business landscape, the significance of digital transformation for Small and Medium-sized Enterprises (SMEs) cannot be overstated. CV Karya Makmur, an Indonesian automotive repair shop, stands at the forefront of this change, recognizing the urgent need to incorporate advanced Information and Communication Technologies (ICTs) into its operations. This transformation is not just about adopting new technologies; it is a comprehensive shift that redefines how the business interacts with customers, optimizes operational processes and improves its overall financial health. The journey of CV Karya Makmur highlights the broader implications of digital transformation in this sector. This case study delves into the multifaceted process of integrating technologies such as augmented reality (AR) and artificial intelligence (AI) to enhance service efficiency, tackle logistical hurdles, and improve access to vital information. Yet, the transition from conventional practices to a digital framework is fraught with obstacles, primarily due to resistance to change. Effective change management, focusing on the human elements of organizational transformation and employee engagement, is pivotal. CV Karya Makmur's experience underscores the critical need for digital systems that promote data-driven decisions, standardize operations, and facilitate better communication. Despite the initial challenges, the potential benefits—increased productivity, reduced operational costs, and a competitive edge in the market—are compelling. This study suggests that considering an organization's unique context and objectives, a tailored digital transformation strategy is essential for leveraging technology to enhance business outcomes in developing countries like Indonesia.